2020
DOI: 10.3390/su12135451
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Student Interventions on Urban Greening Processes

Abstract: The aim of this study is to determine the contribution of student interventions to urban greening processes. In two Dutch cities action research was conducted, including reflexive interviews a year after the first intervention, to assess factors causing change in the socio-ecological system. Results show that students and network actors were mutually learning, causing the empowerment of actors in that network by adding contextualized knowledge, enlarging the social network, expanding the amount of inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
(55 reference statements)
1
6
0
Order By: Relevance
“…In this sense, students’ learning experiences were similar to what Stobbelaar (2020) found when he explored how students organise themselves and share information. A major part of the student projects entailed learning to self-organise.…”
Section: Resultssupporting
confidence: 62%
“…In this sense, students’ learning experiences were similar to what Stobbelaar (2020) found when he explored how students organise themselves and share information. A major part of the student projects entailed learning to self-organise.…”
Section: Resultssupporting
confidence: 62%
“…Additional factors could include unexpected developments (such as the COVID pandemic, etc. ), combined with pressure the micro level (people in the neighbourhoods demanding green spaces, experimenting with green streets [24]), as well as the incremental development on the meso level (politicians wanting to change [22,25] and seeing increasing problems in separate subsystems in a city (see Section 3 for more explanation)). Secondly, solutions for problems in separate subsystems on the meso level must coincide [22,26,27]; problems with climate issues, housing, liveability, green urban infrastructure, transport, etc., must be addressed by integrated solutions.…”
Section: Theoretical Framework: Conditions For Green Urban Transforma...mentioning
confidence: 99%
“…Based on our theoretical framework and literature, we will now stipulate a few measures that can be implemented to speed up transformations towards sustainable green cities. This acceleration needs an interwoven approach to deal with locked-in situations and are also comprehensively described and illustrated by Gorissen et al [24] and Elmqvist et al [10]. Reports by Natuur en Milieu [52], Barboza et al [53], Groene_Stad_Challenge [54], and NL Green label [55] showed the growing importance of green spaces for ecosystem development, health, and well-being.…”
Section: Accelerating Changes Towards Green Citiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It shows that other actors like the municipality take their responsibility for greening seriously, which is also an important factor in behavioural change (social cultural factors). (2) All parties around the inhabitants should send the same message of greening the garden, and should show that they work together [73]. These parties include a municipality, water board, housing cooperation, but also neighbourhood organizations, garden centres and garden television programs.…”
Section: Actors and Measurementsmentioning
confidence: 99%